The Prevalence and Clinical Relevance of the DFS Immunofluorescence Staining Pattern in a Large ANA-Positive Cohort - Deng, Chuiwen; Wang, Anqi; Hu, Chaojun; Zhang, Wen; Zeng, Xiaofeng; Fei, Yunyun (Frontiers in Medicine, 2022)
Background Although the dense fine speckled (DFS) immunofluorescence staining pattern has been studied by various researchers in recent years, its clinical associations remain unspecified. Thus, we performed a retrospective study in a nonselective population to explore the prevalence of this enigmatic antinuclear antibody (ANA) pattern and to determine its possible clinical associations with any identifiable pathology. Methods We retrieved the results of ANA testing ordered by various departments in 2019 to study the prevalence of DFS pattern. Demographic characteristics and clinical features of these participants were also collected from the electronic medical record system. Correlation analysis was made to study its clinical associations and a p value < 0.05 was considered statistically significant. Results The prevalence of ANA positivity was 37.4% among 72204 serum samples of which the median age was 44 (interquartile range:31, 56) years old and 68.0% were females. The prevalence of the DFS staining pattern was 1.1% in the total population and accounted for 3.1% in the ANA-positive population. There were 97.6% of these cases displaying the DFS pattern with a low titre of ANA (≤1:320; starting serum dilution: 1:100). We found that this pattern correlated with several pathological conditions, such as skin disorders (25.1%), alopecia (4.6%) and obstetric complications (6.6%). Conclusion The presence of the DFS immunofluorescence staining pattern may accompany several pathological conditions and may be a signal of localized inflammation within certain organs or tissues, especially the skin.